Women’s Empowerment and Infant and Child Health Status in Sub-Saharan Africa: A Systematic Review - Abreha, Solomon Kibret; Zereyesus, Yacob Abrehe (Maternal and child health journal, 2021)
Introduction Although many studies have examined the relationship between women’s empowerment and a wide range of health outcomes, the extent to which the different dimensions of empowerment influence children’s health, and through which mechanisms and in what contexts, is limited in sub-Saharan Africa. The objective of this review is to systematically assess and examine studies that investigated the association between women’s empowerment and children’s health status in sub-Saharan Africa. Methods A systematic review of the published literature is searched through PubMed, Google Scholar, Embase, Web of Science and Scopus databases focusing on different measures of women’s empowerment and children’s health outcomes. Inclusion criteria in the review are studies that are published in English; full and original articles; studies measuring at least one dimension of women’s empowerment and children’s health outcomes; and Sub-Saharan African context. Studies included in this review are articles published between the year 2000 and 2019. Studies were excluded if the source was a letter, editorial, review, commentary, abstracts without providing full information about the study. Results Initially 4718 citations were identified. Finally, 15 studies met the inclusion and exclusion criteria. In general, the evidence suggests that women’s empowerment at the household level is positively and statistically significantly associated with better children’s health outcomes in sub-Saharan African countries. The review also reveals that women’s decision-making power or autonomy is the most common measure of women’s empowerment employed by many studies. Conclusions Future related studies would benefit by incorporating additional aspects of women's empowerment and child health outcomes.